2015
DOI: 10.1155/2015/424813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin and Sitagliptin on Doxorubicin-Induced Cardiotoxicity in Rats: Impact of Oxidative Stress, Inflammation, and Apoptosis

Abstract: Doxorubicin (DOX) is a widely used antineoplastic drug whose efficacy is limited by its cardiotoxicity. The aim of this study was to investigate the possible protective role of the antidiabetic drugs metformin (250 mg/kg dissolved in DW p.o. for seven days) and sitagliptin (10 mg/kg dissolved in DW p.o. for seven days) in a model of DOX-induced (single dose 15 mg/kg i.p. at the fifth day) cardiotoxicity in rats. Results of our study revealed that pretreatment with metformin or sitagliptin produced significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 40 publications
9
34
0
Order By: Relevance
“…The findings of the present study are in agreement with Aleisa et al [33] who reported that pre-treatment with metformin could improve doxorubicin-induced increase in MDA in mice and Kelle et al [34] who detected the protective effect of metformin could reduce cardiac MDA and the serum level of CK-MB and LDH in doxorubicin treated rats.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study are in agreement with Aleisa et al [33] who reported that pre-treatment with metformin could improve doxorubicin-induced increase in MDA in mice and Kelle et al [34] who detected the protective effect of metformin could reduce cardiac MDA and the serum level of CK-MB and LDH in doxorubicin treated rats.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a previous study using rats showed DOX impairs memory function in novel place recognition [6], and we also detected a specific impairment in the Y-maze task after DOX treatment in rats. We also hypothesized that MET may have a protective effect on DOX-induced impairments in memory function by blocking the metabolic stress response [28], inhibiting the PI-3-kinase-Akt-mTOR (PI3K/Akt/mTOR) pathway, and/or reducing ROS-mediated stress [29]. However, unlike our previous findings using a rat model of CYP-induced cognitive impairment [15], MET did not ameliorate the DOX-induced memory impairment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism and inflammation may not be the only pathomechanisms affected by metformin/NRF2. In fact, other salutary effects have been described for redox (Kocer et al, 2014;Kelleni et al, 2015) and protein homeostasis (Tsai et al, 2017).…”
Section: E Repurposing Instead Of De Novo Drug Discovery and Developmentioning
confidence: 99%